Development and resilience of deciduous Nothofagus forests since the Last Glacial Termination and deglaciation of the central Patagonian Andes - Villa Martinez, Rodrigo Patricio; Moreno, Patricio (My University, 2021)
Resolving the history of vegetation, fire, and glaciation on the eastern slope of the central Patagonian Andes (44 degrees-49 degrees S) since the Last Glacial Termination (T1) has proved difficult. This is due to the steep environmental gradients, vegetation heterogeneity, and scarcity of dated glacial deposits and geomorphic features. Unsurprisingly, published records show important heterogeneities which limit our understanding of the timing and magnitude of climate and vegetation changes, and their driving mechanisms since T1. In this paper, we describe sediment cores from small closed-basin lakes located in the deciduous Nothofagus forest zone near Coyhaique, Chile. Our results indicate that the Coyhaique glacier lobe abandoned its final Last Glacial Maximum position just before similar to 17.9 cal kyr BP and underwent a step-wise recession that included a halt/readvance that culminated at similar to 16.8 cal kyr BP, contemporaneous with the formation of an ice-dammed proglacial lake in the Coyhaique/Balmaceda sector. This glacial lake stood at its highest level between similar to 17.9-17.2 cal kyr BP (<726 and > 650 m.a.s.l.), lowered between similar to 17.2-16.2 cal kyr BP (<650 and > 570 m.a.s.l.), and disappeared thereafter. Herbs and shrubs, currently dominant in high Andean and Patagonian steppe environments, colonized the ice-free terrains distal to the glacier margins and proglacial lakes under cold and dry conditions. This was followed by a steady increase in Nothofagus between similar to 16.6-14.8 cal kyr BP that led to the establishment of forests starting at similar to 14.8 cal kyr BP. The Holocene started with a sudden increase in Nothofagus and disappearance of conifers in the context of increase fire activity between similar to 11.7-9.4 cal kyr BP. Closed-canopy Nothofagus forests persisted virtually unaltered from similar to 9.4 cal kyr BP to the present day, despite frequent explosive volcanism and millennial-scale variations in fire regimes, attesting to their extraordinary postglacial resilience which contrasts with their behavior during T1. Recent large-scale deforestation by fire, livestock grazing, and the spread of non-native invasive plant species drove the fastest and largest-magnitude shifts seen during the last similar to 16,500 years.
Keywords: southern westerly winds; abrupt vegetation change; nothofagus forests; coyhaique/balmaceda proglacial lake; last glacial termination; patagonia